THE CONSTITUTIONAL APPROACH AND HISTORY OF ISLAMIC POLITICAL TO VIOLATIONS OF THE RIGHTS TO RELIGIOUS FREEDOM IN INDONESIA - Hufron Hufron; Abdul Wahid; Mohammad Syaifuddin (Universitas Islam Malang, 2022)
Religious freedom in Indonesia has not been fully respected by every party. There are still a number of parties who address or treat adherents of other religions as individuals or religious groups that deserve to be disturbed in harmony and even if necessary do not have a place to carry out their religious activities. The attitude and behavior of those who are intolerant of disharmony are unconstitutional, which in the study of the history of religious politics in Islam is also contradictory. This unconstitutionality cannot be separated from his feelings and beliefs, which puts parties outside of himself as a lost party or groupKeywords: history, politics. constitution, freedom, religion